Design of a quintuple band microstrip patch antenna using multiple L-slots - A., Mohamed; Islam, Md. Rafiqul; Mohamad, Sarah Yasmin; Badron, Khairayu (IEEE, 2016)
This paper proposes a simple approach to design microstrip patch antenna that can resonate at multiple frequency bands specifically at quintuple resonant frequencies. The antenna is designed to meet five frequency bands which are 0.9GHz, 1.8GHz, 2.1GHz, 2.45GHz and 2.8GHz. The microstrip patch antenna was designed to operate as dual band and a capital L-slot was introduced to design as triple band antenna. Subsequently by adding small l-slots enhanced antenna characteristics to quad band and quintuple bands. The approach is simple and the design of quintuple band antenna consists of a microstrip patch antenna with triple slots inserted on top of the radiating patch. The antenna is designed and simulated using CST Microwave studio. The proposed antenna was fabricated and tested using vector network analyzer. The test result is found close to that obtained by simulation.